2018
DOI: 10.1177/1687814018809184
|View full text |Cite
|
Sign up to set email alerts
|

Engine fault diagnosis based on sensor data fusion considering information quality and evidence theory

Abstract: Fault diagnosis is a problem processing variable information obtained from different sources in nature. Evidence theory, efficient to deal with information viewed as evidence, is widely used in fault diagnosis. However, a shortcoming of the existing fault diagnosis methods only gets probability distribution rather than the basic probability assignment. A novel method of generating basic probability assignment that takes information quality into account is proposed. The probability distribution is determined by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
56
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 94 publications
(56 citation statements)
references
References 71 publications
0
56
0
Order By: Relevance
“…The direct relation is calculated as above. According to the procedures of the DEMATEL method, the direct relation matrix M is normalized in step 2 in Equation (7). And the total relation matrix is calculated in step 3 in Equation (8).…”
Section: Proposed Methodsmentioning
confidence: 99%
“…The direct relation is calculated as above. According to the procedures of the DEMATEL method, the direct relation matrix M is normalized in step 2 in Equation (7). And the total relation matrix is calculated in step 3 in Equation (8).…”
Section: Proposed Methodsmentioning
confidence: 99%
“…It can be concluded that GIQ is more complicated with more information. It should be mentioned that a possible extension of GIQ is to deal with belief function, which is widely used in many real applications…”
Section: Proposed Methodsmentioning
confidence: 99%
“…With the aid of the IQ, the fusion result will be more reasonable which is applied in fault diagnosis …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The belief function is the main mathematical tool for describing the subjective uncertainty phenomenon, the uncertainty . Mainly exists in three basic types, namely the ambiguity, disharmony, and nonspecific…”
Section: Preliminarymentioning
confidence: 99%